2018
DOI: 10.1002/cam4.1712
|View full text |Cite
|
Sign up to set email alerts
|

National Cancer Database report of nonmetastatic esophageal small cell carcinoma

Abstract: BackgroundEsophageal small cell carcinoma (ESCC) is a rare malignancy for which there is no consensus management approach. This is the largest known analysis of nonmetastatic ESCC patients to date, evaluating national practice patterns and outcomes of surgical‐based therapy vs chemoradiotherapy (CRT) vs chemotherapy alone.MethodsThe National Cancer Data Base was queried for esophageal cancer patients with histologically confirmed nonmetastatic ESCC. Univariable and multivariable logistic regression ascertained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…With the application of systemic therapy, researchers have found that adding local surgical resection to systemic treatment significantly improves survival. 22 Although case 2 in this study achieved significant remission after treatment, pCR was not achieved. Surgical resection may have potential benefits in preventing recurrence.…”
Section: Discussionmentioning
confidence: 58%
“…With the application of systemic therapy, researchers have found that adding local surgical resection to systemic treatment significantly improves survival. 22 Although case 2 in this study achieved significant remission after treatment, pCR was not achieved. Surgical resection may have potential benefits in preventing recurrence.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, several studies have showed that surgical resection was beneficial. 13 , 14 Verma et al 15 have indicated that adding surgery or radiotherapy to chemotherapy led to improved long‐term survival outcomes. In addition, Chen et al 16 have reported that surgical resection alone was adequate for patients with early‐stage SCCE.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rarity and tumour heterogeneity of SCEC, a specific staging system, clinical trials, or standard treatment have not as yet been established. Additionally, as SCEC is a highly aggressive malignancy with dismal survival, considerable controversy regarding its prognostic factors exists, with the few studies investigating this being retrospective, with small sample size, and producing inconsistent results (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%